(untitled) (Acta Scientiarum. Health Sciences, 2025)
This research seeks to analyze the socioeconomic profile of e-cigarette users, their frequency of use and symptoms induced by e-cigarettes. It is composed of 562 participants and divided into three stages: approach via social media, data collection by means of a self-administered online questionnaire, and descriptive data analysis. The demographic profile was characterized by young university students with higher education and middle/upper class income. The most prevalent symptoms were throat irritation and/or hoarseness (56.3%), cough (57.4%), nasal congestion (27.6%), anxiety (21.4%). In conclusion the results verified the association of demographic profile aspects, which pointed to a tendency for older individuals with a higher socioeconomic status to present more symptoms resulting from the use of electronic cigarettes; a greater proportion of individuals who reported not having knowledge about the composition of e-liquids was found, and this fact was associated with a greater presence and prevalence of symptoms harmful to health.